Rotavirus infection-associated central nervous system complications: clinicoradiological features and potential mechanisms - Kyung Yeon Lee (Clinical and Experimental Pediatrics, 2022)
Despite the introduction of vaccines in 2006, rotavirus remains one of the most common causes of pediatric gastroenteritis worldwide. While many studies have conclusively shown that rotavirus infection causes gastroenteritis and is associated with various extraintestinal manifestations including central nervous system (CNS) complications, extraintestinal manifestations due to rotavirus infection have been relatively overlooked. Rotavirus infection-associated CNS complications are common in children and present with diverse clinicoradiological features. Rotavirus infection-associated CNS complications can be classified based on clinical features and brain magnetic resonance imaging findings, particularly lesion location on diffusion-weighted imaging. Common clinicoradiological features of rotavirus infection-associated CNS complications include: (1) benign convulsions with mild gastroenteritis; (2) acute encephalopathies/encephalitis, such as mild encephalopathy with a reversible splenial lesion, acute encephalopathy with biphasic seizures and late reduced diffusion, and acute necrotizing encephalopathy; (3) acute cerebellitis; and (4) neonatal rotavirus-associated leukoencephalopathy. The precise mechanism underlying the development of these complications remains unknown despite a number of clinical and laboratory studies. Here we review the diverse clinicoradiological features of rotavirus infection-associated CNS complications and propose a hypothesis of their pathophysiology.